The effectiveness of two contrasting mulch application rates to reduce post-fire erosion in a Portuguese eucalypt plantation - Keizer, J.J. (2020)
Wildfires are well-known to increase runoff and erosion during the initial stages of the window-of-disturbance, and mulching has been widely documented to effectively minimize this impact. However, the relationship between the rate of mulch application and erosion reduction is poorly studied, in spite of its potential importance for optimizing mulching costs and efforts per ha. Therefore, a field experiment was carried out in a recently burnt eucalypt plantation in Central Portugal that had been burnt by a moderate severity fire during August 2015, comparing sediment as well as organic matter losses from three untreated 2 m × 8 m erosion plots with losses from six plots mulched with eucalypt logging residues at two contrasting rates of either 2.6 or 8.0 Mg ha–1. The two mulching treatments resulted in the targeted litter covers of 50 and 79%, and these covers hardly changed over the ensuing year. Over this first post-fire year, the mulched plots produced significantly less mineral soil as well as organic matter losses than the untreated plots. At the same time, the plots with the high mulching rate lost consistently less sediments and organic matter than the plots with the low mulching rate but the differences were not statistically significant over all measurement periods. Total sediment losses over the first post-fire year were, on average, 86 and 96% lower following mulching at 2.6 and 8.0 Mg ha–1, respectively, than without mulching. In absolute values, total losses dropped from 8.0 to 1.1 and 0.3 Mg ha–1 y–1, respectively, or, in other words, similar to and well-below the widely-accepted threshold of tolerable soil loss of 1 Mg ha–1 y–1. If this threshold value is acceptable to land managers, they could treat a three times larger area with the same amount of mulch.